Design of XS2 (X = W or Mo)‐Decorated VS2 Hybrid Nano‐Architectures with Abundant Active Edge Sites for High‐Rate Asymmetric Supercapacitors and Hydrogen Evolution Reactions. Issue 8 (11th December 2022) - Hussain, Sajjad; Vikraman, Dhanasekaran; Sarfraz, Maria; Faizan, Muhammad; Patil, Supriya A.; Batoo, Khalid Mujasam; Nam, Kyung‐Wan; Kim, Hyun‐Seok; Jung, Jongwan
Abstract: Two‐dimensional layered transition metal dichalcogenides have emerged as promising materials for supercapacitors and hydrogen evolution reaction (HER) applications. Herein, the molybdenum sulfide (MoS2 )@vanadium sulfide (VS2 ) and tungsten sulfide (WS2 )@VS2  hybrid nano‐architectures prepared via a facile one‐step hydrothermal approach is reported. Hierarchical hybrids lead to rich exposed active edge sites, tuned porous nanopetals‐decorated morphologies, and high intrinsic activity owing to the strong interfacial interaction between the two materials. Fabricated supercapacitors using MoS2 @VS2  and WS2 @VS2  electrodes exhibit high specific capacitances of 513 and 615 F g − 1, respectively, at an applied current of 2.5 A g − 1  by the three‐electrode configuration. The asymmetric device fabricated using WS2 @VS2  electrode exhibits a high specific capacitance of 222 F g − 1  at an applied current of 2.5 A g − 1  with the specific energy of 52 Wh kg − 1  at a specific power of 1 kW kg − 1 . For HER, the WS2 @VS2  catalyst shows noble characteristics with an overpotential of 56 mV to yield 10 mA cm − 2, a Tafel slope of 39 mV dec −1, and an exchange current density of 1.73 mA cm − 2 . In addition, density functional theory calculations are used to evaluate the durable heterostructure formation and adsorption of hydrogen atom on the various accessible sites of MoS2 @VS2  and WS2 @VS2  heterostructures. Abstract : Novel hierarchical lamellar MoS2 @VS2  and WS2 @VS2  heterostructures bonded through strong interfacial interaction of MoS2  and WS2  with layered VS2  nanosheets are achieved via a hydrothermal reaction process. A high asymmetric specific capacitance of 222 F g − 1 and outstanding hydrogen evolution reaction characteristics are realized for the designed WS2 @VS2  hybrid.